Water Resources of Tajikistan and Water Use Issues in Central Asia - H. M. Mukhabbatov (Проблемы постсоветского пространства)
This paper investigates the formation and use of water resources in Tajikistan. The natural and geographic conditions as well as distribution of water resources across the economic regions are analyzed. It is stressed that after breakup of the Soviet Union the water use issues in Central Asia have acquired the dimensions of the interstate economic and political problems. Demographic growth, activation of desertification, global warming make most relevant the issue of equitable redistribution of water resources as the most valuable resource for economy.